2011
DOI: 10.1093/gerona/glr017
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fish Oil Modestly Attenuates the Effect of Age on Diastolic Function but Has No Effect on Memory or Brain Inflammation in Aged Rats

Abstract: Fish oil (FO) mediates a number of cardioprotective benefits in patients with cardiovascular disease. In the absence of cardiovascular disease, however, the effects of FO on cardiac structure and function are not clear. In addition, it is not known if an effective dosing strategy for attenuating age-related cardiac dysfunction is also effective at limiting cognitive dysfunction. Therefore, we determined if 4 months of FO supplementation in aged rats would lessen age-related cardiac dysfunction while concomitan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…In leukocytes, n -3 PUFA decreased pro-inflammatory gene activation by altering membrane order, reducing eicosanoid and diacylglycerol synthesis, inhibiting specific isoforms of protein kinase C and mitogen-activated protein kinases, increasing the phosphorylation of phospholipase C-γ, a key signaling enzyme [ 75 ]. Many other complex mechanisms in cellular signaling have been postulated in studies investigating the neuroprotective effects of n -3 PUFA in Alzheimer’s disease [ 112 ], including inhibition of neuro-inflammation [ 113 ], although some studies in model animals have given negative results [ 114 ]. The link among n -3 PUFA, neuro-inflammation and dementia is also supported by observational data from the InCHIANTI study, where low serum n -3 PUFA levels have been cross-sectionally associated with both CRP elevation [ 86 ] and poor cognitive function [ 115 ].…”
Section: N -3 Polyunsaturated Fatty Acids and Imentioning
confidence: 99%
“…In leukocytes, n -3 PUFA decreased pro-inflammatory gene activation by altering membrane order, reducing eicosanoid and diacylglycerol synthesis, inhibiting specific isoforms of protein kinase C and mitogen-activated protein kinases, increasing the phosphorylation of phospholipase C-γ, a key signaling enzyme [ 75 ]. Many other complex mechanisms in cellular signaling have been postulated in studies investigating the neuroprotective effects of n -3 PUFA in Alzheimer’s disease [ 112 ], including inhibition of neuro-inflammation [ 113 ], although some studies in model animals have given negative results [ 114 ]. The link among n -3 PUFA, neuro-inflammation and dementia is also supported by observational data from the InCHIANTI study, where low serum n -3 PUFA levels have been cross-sectionally associated with both CRP elevation [ 86 ] and poor cognitive function [ 115 ].…”
Section: N -3 Polyunsaturated Fatty Acids and Imentioning
confidence: 99%
“…These studies suggested that ω3 fatty acids dietary supplementation is able to limit the apparition of cognitive deficit, even when the administration starts at old age. Conversely, some studies using fish oil supplementation did not reveal improvement of spatial learning or memory in the Morris water maze test in aged rodents (Barceló-Coblijn et al, 2003;Calon et al, 2003;Sergeant et al, 2011). Finally, it is noteworthy that in the study with aged monkeys supplemented with DHA (Tsukada et al, 2000), only 4 weeks of treatment led to increased regional cerebral blood flow, a parameter closely linked to neuronal activation.…”
Section: ω3 Supplementation and Cognitive Performances In Aged Mouse mentioning
confidence: 98%